Luminescence spectroscopy measurements for skin cancer research - Kałużyński, Piotr Dariusz; Opilski, Z.; Niedzielska, I.; Sitek-Ignac, N.; Kogut, D. (Photonics Letters of Poland, 2018)
In this paper we present a simple design of skin cancer optical probe diagnostic system, which use a non-invasive optical method of detection. This method can be used to image of malignancies based on luminescence spectroscopy analysis of given tissues. Through a comparative analysis of red and green peaks in given spectra, the detection of cancerous tissues can be increased. Proposed method and given luminescence spectra, shows that this system can be used, as one of the criteria for early skin cancer diagnosis. Full Text: PDF References A. Sieroń, W. Stręk, H. Podbielska, Urban&Partner (2004). DirectLink A. Profio, "Laser excited fluorescence of hematoporphyrin derivative for diagnosis of cancer", IEEE Journal of Quantum Electronics (1984), CrossRef Palmer S, "Optical redox ratio and endogenous porphyrins in the detection of urinary bladder cancer: A patient biopsy analysis", Journal of Biophotonics (2017) CrossRef M. A. D'Hallewin, "Fluorescence Detection of Bladder Cancer: A Review", European Urology, (2002) CrossRef M. Monici, "Cell and tissue autofluorescence research and diagnostic applications", Biotechnology Annual Review, (2005) CrossRef Croce A.C., Bottiroli G., "Autofluorescence spectroscopy and imaging: a tool for biomedical research and diagnosis", European Journal of Histochemistry (2014) CrossRef Bottiroli G, Croce AC. Photosciences, lasers and current optical techniques in biology (2004). CrossRef R.A. Drezek, K. V. Sokolov, U. Utzinger, I. Boiko, A. Malpica, M. Follen, R. R. Richards-Kortum, "Understanding the contributions of NADH and collagen to cervical tissue fluorescence spectra: modeling, measurements, and implications", Journal of Biomedical Optics (2001). CrossRef